A105 CANADIAN WOMEN WITH IBD ARE MORE LIKELY TO GIVE BIRTH TO LOW BIRTH WEIGHT INFANTS. (1st March 2018) - Targownik, L E; Benchimol, E I; Seow, C; Nguyen, G C; Pena-Sanchez, J; Jones, J; Metcalfe, A; Dolovich, C; Bernstein, C N; Singh, H
Abstract: Background: Inflammatory bowel disease (IBD), a chronic inflammatory disease, often develops in adolescence and young adulthood, thus affecting many women in their childbearing years. Data are conflicting on the effect of IBD on gestational outcomes. Population-based data evaluating perinatal outcomes among Canadian women with IBD in the modern era are lacking. Aims: We sought to determine whether there is an increased likelihood of prematurity and/or low birth weight among infants born to Canadian women with IBD in a population based provincial dataset Methods: We used the University of Manitoba IBD Epidemiologic Database to identify all women in Manitoba between the ages of 15 to 45 with either Crohn's disease (CD) or ulcerative colitis (UC) between 1984–2014. Women with IBD were matched to non-IBD controls in a 1:10 ratio on age and neighbourhood of residence at the time of IBD diagnosis. Live birth events were identified in the maternal record and linked to the neonatal record to obtain the estimated gestational age and birth weight. Prematurity was defined as gestational age less than 37 weeks. Infants weighing less than 2500g at birth were considered to have low birth weight (LBW), and those weighing between 2500-3000g were classified as low-normal birth weight (LNBW). The proportion of all LBW and premature babies among all babies born was calculated for IBD (stratified for CD and UC) and controls. Results: There were 3172 women with IBD (1, 827 CD, 1, 345 UC) matched to 27, 184 non-IBD controls (15, 802 matched to CD cases, 11, 382 matched to UC cases), 1495 infants (878 CD, 617 UC) were born to women with IBD, compared with 14, 006 infants born to controls (8, 362 CD controls, 5, 644 UC controls). 3.5% of infants born to women with CD were premature, compared with 1.9% of controls (p=0.0043); There was no significant difference in the likelihood of prematurity among babies born to women with UC compared with their controls (2.9% vs. 2.3%, p>0.2). The probability of having a LBW infant was higher among both women with CD and UC compared with controls (CD: 7.8% vs 3.4%, p=0.0004; UC: 7.0% vs 3.1%, p=0.0033). There was also a higher prevalence of LNBW babies among CD (17.5% vs 10.9%, p=0.0008) and UC (18.2% vs 12.5%, p=0.009). Neither maternal age at birth nor era of birth were associated with prematurity, LBW, or LNBW Conclusions: Canadian women with IBD are at increased risk of having LBW and LNBW infants, and women with CD specifically have a higher chance of giving birth prematurely. Further work is required to determine the disease and treatment related factors which may predispose to the development of these adverse birth outcomes. Funding Agencies: American College of Gastroenterology and the Canadian Gastrointestinal Epidemiologic Consortium